TINOSPORA CORDIFOLIA: A CLIMBING SHRUB IN HEALTH CARE MANAGEMENT - MUKESHWAR PANDEY,; SURENDRA K. CHIKARA,; MANOJ K. VYAS,; ROHIT SHARMA,; GULAB S. THAKUR,; P. S. BISEN, (International Journal of Pharma and Bio Sciences, 2012)
Tinospora cordifolia is a deciduous climbing shrub described as ‘the one who protects the body against diseases’. It is one of the most versatile rejuvenating shrub also known as ’Giloya’ in Indian vernacular having many therapeutic applications. The pharmaceutical significance of this plant is mainly because of the leaves, barks and roots contain various bioactive compounds such as alkaloids, glycosides, lactones, steroids, polysaccharides and aliphatic compounds having various medicinal importance viz. immunomodulatory or immunostimulatory, antitumor, cognition, anti-inflammatory, anti-neoplastic, antihyperglycemia, antihyperlipidemia, antioxidant, anti-tuberculosis, gastrointestinal and hepatoprotection, anti-osteoporotic, anti-angiogenic, anti-malarial, anti-allergic and side effects prevention of the cancer chemotherapy. The bitter priniciples present in the leaves, stems, roots and barks viz. tinosporine, tinosporide, tinosporaside, cordifolide, cordifol, berberine, cordifolioside A, B. C, amritosides A, B, C, and columbin which act as therapeutic agents and play vital role in many therapeutic applications. Various parts of the plant are being prescribed in Ayurveda and other systems of medicine as a monoherbal or polyherbal preparation. The climbing shrub has shown a great potential for the development of industrial products and commercial exploitation of biopharmaceuticals for the treatment of various diseases. The focus of the present review is to galvanize the potential of medicinal importance of this shrub for health care management.